Zooplankton Genera from Sematan River, Sarawak : A Preliminary Inventory - Mohd Nasarudin, Harith; Nurul Syaza, Zainol; Ahmad Syafiq, Ahmad Nasir; Nazri, Latib; Mohamad Norazlan, Bujang Belly; Nur Atiqah, Mohamad Yusoff. (UTS Publisher, 2025)
The present study provides a baseline inventory of zooplankton genera and their abundance, based on data collected during the dry (August 2010) and wet (January 2011) seasons from six stations in the Sematan River, Sarawak, Malaysia. Despite the age of the data, this study represented the only known record of zooplankton diversity in the river, offering a valuable reference for monitoring ecological changes over time. A total of 14 genera belonging to four taxa were identified, with Copepoda dominating the assemblages, contributing 68.44% of the total abundance. Among the genera, Limnocalanus was the most abundant, comprising 29.56% of the total count, followed by Diaptomus and Macrothrix. However, zooplankton abundance was significantly higher during the dry season, particularly at Stations 3 and 4, likely due to influenced by environmental conditions such as light availability and water flow. The finding of this inventory would serve as a critical reference for future biodiversity assessments and comparative studies in the region, particularly in light of potential environmental changes over the past decades. Although the data were collected in 2010 and 2011, they serve as a valuable baseline for future ecological comparisons and assessments in this relatively understudied tropical river.